The Influence of Development of Alutsista, Digital Capability, and Work Hapiness on Military Effectiveness Through Job Simplification as An Intervening Variable (Case Study in Batalion Intai Amfibi 2 Korp Marinir Surabaya) - Abiantoro, Bayu; Mujanah, Siti; Ardiana, Dewa Ketut Raka (PT Inovasi Pratama Internasional, 2025)
The military is one of the main pillars in maintaining the sovereignty and security of a country. The Indonesian National Army (TNI), which consists of three main forces (Army, Navy and Air Force) has an important function in maintaining security on land, sea and air. This research aims to analyze the influence of Alutsista Development, Digital Capability and Work Happiness on Military Effectiveness and Job Simplification. The population in this study were soldiers in the Batalion Intai Amfibi 2 Korps Marinir Surabaya total 100 soldiers using a saturated sample. Hypothesis testing in this research was carried out using a Structural Equation Model (SEM) approach based on Partial Least Square (PLS). Based on the 7 direct influence hypotheses processed in this research, there are 3 hypotheses which state that the influence is not significant while the other 4 hypotheses state that the influence is significant. The results of this research indicate that Alutsista Development and Work Happiness partially have an insignificant effect on Job Simplification. Meanwhile, Digital Capability has a significant positive effect on Job Simplification. Then Alutsista development, digital capability and job simplification partially has a significant positive effect on military effectiveness. Meanwhile, Work Happiness has no significant effect on Military Effectiveness.